2015
DOI: 10.1093/mnras/stv2695
|View full text |Cite
|
Sign up to set email alerts
|

SAX J1808.4−3658, an accreting millisecond pulsar shining in gamma rays?

Abstract: We report the detection of a possible gamma-ray counterpart of the accreting millisecond pulsar SAX J1808.4-3658. The analysis of ∼6 years of data from the Large Area Telescope on board the Fermi Gamma-ray Space Telescope (Fermi-LAT) within a region of 15• radius around the position of the pulsar reveals a point gamma-ray source detected at a significance of ∼6σ (Test Statistic TS = 32), with position compatible with that of SAX J1808.4-3658 within 95% Confidence Level. The energy flux in the energy range betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Among previous searches for γ-ray emission from neutron star X-ray binaries (e.g., Xing & Wang 2013;de Oña Wilhelmi et al 2016), Li et al (2012) have provided a very similar case to GRO J1008−57 by justifying that the γ-ray transients GRO J1036−55 and AGL J1037−5708 are associated with the HMXB 4U 1036−56. The likely association indicates that the HMXB only had occasional (detectable) γ-ray emission during several days.…”
Section: Discussionmentioning
confidence: 99%
“…Among previous searches for γ-ray emission from neutron star X-ray binaries (e.g., Xing & Wang 2013;de Oña Wilhelmi et al 2016), Li et al (2012) have provided a very similar case to GRO J1008−57 by justifying that the γ-ray transients GRO J1036−55 and AGL J1037−5708 are associated with the HMXB 4U 1036−56. The likely association indicates that the HMXB only had occasional (detectable) γ-ray emission during several days.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism to expel the accreting matter from the system involves radiation pressure of the magneto-dipole rotator that should power the NS during quiescence phases (see e.g., Burderi et al 2003;Di Salvo et al 2008). Over the years several indirect hints that in SAX J1808.4-3658 the radio pulsar mechanism turns on during quiescence phases have been collected, e.g., the presence of an over-luminous optical counterpart of the source (Homer et al 2001) interpreted by Burderi et al (2003) as the spin-down luminosity of the magneto-dipole rotator reprocessed by the companion star; the secular spin-down evolution of the NS spin showing derivative values typical of millisecond radio pulsars (Hartman et al 2009b;Patruno et al 2012); detection of a possible gamma-ray counterpart of the source as observed by Fermi-LAT during the quiescence phases of SAX J1808.4-3658 (de Oña Wilhelmi et al 2016;Xing et al 2015). Nonetheless, although carefully searched (Burgay et al 2003;Patruno et al 2016), no direct observation of the radio pulsar activity of the source has been observed to date (at this moment the only known AMXP observed as rotation-powered pulsar is IGR J18245-2453, Papitto et al 2013).…”
Section: Radio-ejection Mechanismmentioning
confidence: 99%
“…In recent works, Xing et al (2015) and de Oña Wilhelmi et al (2016)identified a possible gamma-ray counterpart of SAX J1808.4−3658, and spectral modeling of the Fermi Large Area Telescope (FERMI/LAT) data impliesthat (if the counterpart is confirmed) about 30% of the spin-down energy is transformed into gammarays, providing further evidence in favor of this scenario, although no gamma-ray pulsations have been found so far.…”
Section: Introductionmentioning
confidence: 98%